Contraceptive counseling: construction and validation of instrument—“5C contraceptive counseling” - Palma, Sara (2024)
Introduction: Contraceptive illiteracy leads to non-adherence, discontinuation, and dissatisfaction with the method. Person-centered contraceptive counseling is based on quality care on a communicative basis that promotes shared decision-making, leading to a choice adapted to the woman’s needs, lifestyle, and health condition. We intend to build and validate an instrument that serves as a guide for quality contraceptive counseling, facilitating decision-making about contraceptive methods. Methods: We used the Delphi method in a total of two rounds. The content was validated through a panel of eighteen experts with experience in teaching, research in contraceptive counseling, and obstetric nursing. To assess the consensus and stability of the responses, two questionnaires were administered and the Content Validity Index and Content Validity Ratio were calculated. Results: The initial version of the guide, consisting of six indicators and thirty-five items, was submitted to the panel of experts to obtain consensus and stability from respondents (first round). The results showed a response rate of 66.0%; thirty-four indicators reached consensus and one did not reach consensus. Suggestions for modifying the indicator were received by the experts and incorporated in the next round. In the second round, the response rate increased to 78.0%. Two indicators were resubmitted, of which one was accepted. This resulted in the final version of the instrument, with six points and thirty-five items. Discussion: The guide proved to be a valid tool for nurse–midwives to provide quality contraceptive advice to women, allowing them to make autonomous and informed choices regarding their sexual and reproductive health.